Effect of Dispersants on the Physical Stability of Cupric Oxide Aqueous Suspensions. Issue 2 (3rd April 2017) - Liu, Zequan; Zhang, Qiang
ABSTRACT: CuO suspensions were prepared with various dispersants, viz. sodium salt of styrene/ methacrylic acid copolymer, hexadecyl trimethyl ammonium bromide, sodium dodecyl sulfonate and polysorbate. Zeta potential analyzer, multiple light scattering measurement (Turbiscan Lab) and scanning electron microscope were used to study the zeta potential and suspension stability of CuO aqueous system in the presence of dispersants. It is shown that sodium salt of styrene/methacrylic acid copolymer is the most efficient dispersant for CuO suspension, and when the dosage of sodium salt of styrene/methacrylic acid copolymer is 10 wt% of CuO powders and pH is 9, the highest suspension stability of CuO suspension is obtained. GRAPHICAL ABSTRACT: